Characteristic comparison of cornstarch-based bioplastics using kaolin, microcrystalline cellulose and chitosan as fillers - Mai Anugrahwati; Meilani Dwi Putri Nasution; Febi Indah Fajarwati (Jurnal Pijar Mipa, 2022)
In the study, the basic material for making bioplastics was corn starch with the addition of kaolin, microcrystalline cellulose, and chitosan as filler variations, as well glycerol as a plasticizer. The method used was the blending method. The characterization included the absorption test for water resistance, biodegradation test, tensile and elongation strength test, and functional group analysis using FTIR. Among fillers, the best bioplastic characteristic bioplastic was obtained with filler kaolin with the water absorption value of 88.62%, a tensile strength value of 1.44 x10-3 MPa, and the elongation strength value of 5.04%. Nearly 80% of the material was degraded in 15 days. Spectra of FTIR showed the appearance of some functional groups from starch, filler, and plasticizer, which meant that the process of bioplastic manufacturing was physical mixing.